77 Improving recogntion and end of life care coordination across 3 ccgs. evaluation of our service. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Wilson, Linda; Gilkes, Hazel
Abstract : Introduction: In Airedale, Bradford and Craven we have been developing end of life care services at a population level, aiming to identify, offer sensitive conversations and care coordination via a 24/7 hub based at an acute hospital (Gold Line) to as many patients as possible who are in the months/year of life. Method: Multiple interventions to support identification, communication and care planning for all patients thought to be in the last year of life across primary and secondary care. Includes communication skill training via Sage and Thyme, bespoke sessions for senior clinicians and one of two of NHS England Serious Illnesses care pilot sites. Use of EPACCS end of life template. Provision of 24 hour support hub. Support for primary care EOL MDT meetings via EOL facilitation in 1 CCG. Results: Please refer to attached documents. 1 CCG now has 68% of all deaths (90% 'predictable' deaths) identified, registered on EPaCCS and receiving care. This CCG also has the lowest% hospital deaths in England. One CCG is less well engaged. Discussion: Multiple interventions to identify, communicate and provide coordinated care have been successful in increasing the number of patients and their carers receiving support in the last year of life. Use of a 24 hour hub provided by non-specialist staff appears to we well received and successful. Quality of care provided to individuals now needs to be measured.